2014
DOI: 10.1097/pai.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of SFRP1 and SFRP3 Proteins in Normal and Malignant Reproductive Tissues of Rats and Humans

Abstract: Secreted frizzled-related proteins 1 and 3 (SFRP1 and SFRP3) act as Wnt signaling pathway antagonists and play an important role in embryonic development and carcinogenesis. The aim of the present study was to analyze immunohistochemically the distribution of 2 SFRP family proteins, SFRP1 and SFRP3, in an experimental rat model, in normal and intrauterine growth-restricted (IUGR) human placentas, and in a subset of the corresponding human trophoblastic tumors (pure choriocarcinomas and mixed germ cell tumors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…SFRP proteins antagonize the canonical Wnt signaling through binding to its components, thereby inhibiting their downstream signaling activities . We previously reported that germ cell tumors with trophoblastic differentiation (choriocarcinomas) frequently exhibit loss of SFRP1 and SFRP3 proteins . In the present study, we tested a cohort of germ cell tumors of the testis and found a substantial loss (median expression in tumor cells ~5–10%) of both proteins in comparison with adjacent atrophic/benign testicular tissue.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…SFRP proteins antagonize the canonical Wnt signaling through binding to its components, thereby inhibiting their downstream signaling activities . We previously reported that germ cell tumors with trophoblastic differentiation (choriocarcinomas) frequently exhibit loss of SFRP1 and SFRP3 proteins . In the present study, we tested a cohort of germ cell tumors of the testis and found a substantial loss (median expression in tumor cells ~5–10%) of both proteins in comparison with adjacent atrophic/benign testicular tissue.…”
Section: Discussionmentioning
confidence: 58%
“…Wnt signaling pathway plays an important role in the differentiation of the testis as well as spermatogenesis. The status of SFRP and DVL proteins is largely unknown in testicular germ cell tumors, with only a few published studies that show loss of SFRP1 protein expression in testicular tumors , whereas expression of DVL1 and DVL2 has not been examined, to our knowledge. In this study, we aim to investigate the expression of SFRP1, SFRP3, DVL1, and DVL2 proteins in germ cell tumors of the testis.…”
mentioning
confidence: 94%
“…Frizzled-related protein 3 (FRP-3) is a member of the Wnt signaling pathway and plays important roles during cardiac embryogenesis. Expression of FRP-3 in ECs has also been confirmed by immunohistological staining in reproductive tissues (Partl et al, 2014 ). Currently, there are no known effects of FRP-3 on cardiac contractility, but it has been shown that FRP-3 expression is increased in failing human myocardium, with a decline following LV assist device therapy (Askevold et al, 2014 ), indicating that FRP-3 is related to heart failure progression, and its secretion dependent on ventricular wall strain.…”
Section: Endothelium-derived Proteins Modulating Cardiac Contractilitmentioning
confidence: 83%
“…In placenta, sFRP3 expression was confined to blood vessel endothelial cells, while decidual cells showed only occasional weak cytoplasmic staining. Perimetrium and myometrium were also positive for sFRP3 expression [ 37 ]. We demonstrated that DVL3 and sFRP3 proteins were present in glioblastoma tissue samples.…”
Section: Resultsmentioning
confidence: 99%